2005
DOI: 10.2219/rtriqr.46.219
|View full text |Cite
|
Sign up to set email alerts
|

Development of Tilt Control System Using Electro-Hydraulic Actuators

Abstract: To improve the performance and riding comfort of tilt-controlled vehicles, we developed a next-generation tilt control system that uses a position detecting system, a novel tilt pattern, high performance tilt actuators and other new technical elements. Under this system, the running train position is detected by curvature collation based on GPS signals and the tilting angle target pattern calculated to optimize the riding comfort evaluation index. The pattern thus created is called the JT pattern, according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…Comparison of electric and hydraulic actuators is given in [33]. The following comparison is given for active tilt control applications.…”
Section: Comparison Of Hydraulic and Servo Motor Actuatorsmentioning
confidence: 99%
“…Comparison of electric and hydraulic actuators is given in [33]. The following comparison is given for active tilt control applications.…”
Section: Comparison Of Hydraulic and Servo Motor Actuatorsmentioning
confidence: 99%
“…Tilting trains, which have tilting mechanism of carbody to compensate for the shortage of cant when speed-up on sharp curves, are introduced for such purpose; in early times, natural pendulum type mechanisms using centrifugal force itself for tilting action were applied to commercial trains in Japan. Although the natural pendulum type of tilting trains contributed to increase speed in curved sections, it was found that they had matters to induce some passengers' comfort in curved section [36,37] and high-performance actuator [38,39] with good response to the tilting command are both important in improving performance and ride quality of tilting trains.motion sickness. This was considered caused by the delay of tilting motion at the entry and exit of a curve due to mechanical non-ideality such as friction.…”
Section: Application Of Control Techniquesmentioning
confidence: 99%
“…Ураховуючи наявність двох електромеханічних частин та двох пневморесор, диференційно-алгебраїчна система рівнянь, що визначає узагальнену математичну модель електромеханічної частини механізму нахилу, які наведено у [18,19], остаточно, набуває вигляду:…”
Section: рис 1 схема комбінованого механізму нахилу кузоваunclassified
“…В даний час приводи нахилу кузовів застосовуються на електропоїздах, що експлуатуються в багатьох країнах світу, включаючи Австралію [9], Німеччину [6], Іспанію [8], Італію [7], Канаду, Китай [11,12], Норвегію, Португалію, Словенію, США, Фінляндію [2,4], Францію [13], Швейцарію [14][15][16], Швецію [17] та Японію [18,19]. Таким чином, робота направлена на розвиток систем нахилу кузовів рухомого складу, є актуальною для розвитку швидкісного руху на залізницях в усьому світі.…”
unclassified